2022
DOI: 10.15402/esj.v8i3.70753
|View full text |Cite
|
Sign up to set email alerts
|

Leveraging Community-University Partnerships to Develop a Strength-Based and Individualized Approach to Humanizing Housing Service Delivery for Individuals with Fetal Alcohol Spectrum Disorder (FASD)

Abstract: This field report summarizes and advances key learnings for leveraging community–university partnerships addressing housing service gaps for high-risk, marginalized populations with complex needs. We describe our navigation of existing and forged intersections to develop a strength-based and individualized approach to humanizing housing service delivery for individuals with fetal alcohol spectrum disorder (FASD). Our account is framed by four questions: why community and university partners came together to de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
8
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 7 publications
1
8
0
Order By: Relevance
“…Caregivers shared grave concerns about the future of the adults they support when they are no longer able to provide care due to aging or death, as well as their hopes that the adults with FASD they support would find housing where they are safe, loved, and feel at home. This study's findings align with previous recommendations (e.g., Brownstone, 2005;Burns, 2009;Pei et al, 2018) and support the importance of developing FASD-informed housing supports (Rutman, 2016).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Caregivers shared grave concerns about the future of the adults they support when they are no longer able to provide care due to aging or death, as well as their hopes that the adults with FASD they support would find housing where they are safe, loved, and feel at home. This study's findings align with previous recommendations (e.g., Brownstone, 2005;Burns, 2009;Pei et al, 2018) and support the importance of developing FASD-informed housing supports (Rutman, 2016).…”
Section: Discussionsupporting
confidence: 90%
“…Understanding FASD and person-centered support Supports with an understanding of FASD demonstrate awareness of the varied ways in which FASD can impact someone's strengths and needs, and strive to adapt their environments to optimize strengths and better support challenges (Rutman, 2016). Canadian FASD housing reports by Brownstone (2005), Burns (2009), andPei et al (2018) each emphasize the importance of developing a spectrum of supports for adults with FASD in response to variability in strengths and challenges. In line with reports, the critical nature of understanding the diverse impacts of FASD was pervasive throughout this study.…”
Section: Fasd-informed Supportmentioning
confidence: 99%
See 1 more Smart Citation
“…Participants in this study and previous research have repeatedly emphasized the need for supportive services developed with an understanding of the diverse strengths and challenges experienced by individuals with FASD (Cleversey et al., 2018; Malbin, 2011; Pei et al., 2018; Pruner et al., 2020). Adults with FASD interviewed in this study highlighted their appreciation of supportive people who demonstrated an understanding of the unique and varied ways FASD influences their strengths and needs for support.…”
Section: Discussionmentioning
confidence: 94%
“…Participants in this study and previous research have repeatedly emphasized the need for supportive services developed with an understanding of the diverse strengths and challenges experienced by individuals with FASD (Cleversey et al, 2018;Malbin, 2011;Pei et al, 2018;Pruner et al, 2020).…”
Section: Fasd-informed Housing Supportmentioning
confidence: 99%